Financial Satisfaction of SMEs in The Coastal Region of Madura: Financial Management Behavior and Financial Knowledge - Hanum, Faricha; Purnamawati, Purnamawati; Gitayuda, M. Boy Singgih (UMSurabaya Publishing, 2024)
In the current 4.0 era, good economic growth is one of the standards for the government's success in achieving development goals, including the economic aspect. One of the government's efforts is to create and comprehensively support MSME activities. MSMEs on the island of Madura are growing yearly in terms of quantity, quality and sales of MSME products that have entered foreign markets. This research aims to analyze the influence of financial management behaviour and financial knowledge on the financial satisfaction of MSME actors in the Madura coastal area. Data were analyzed using quantitative methods with descriptive and associative approaches. Data was received from the results of interviews and filling out questionnaires by MSME actors in the Madura coastal area in Pamekasan Regency and Sumenep Regency, totalling 60 respondents. The data was processed with the help of smartPLS 3 software. The findings from this research are that financial management behaviour and financial knowledge positively influence financial satisfaction.